Biosynthesis of α-Gal Epitopes (Galα1-3Galβ1-4GlcNAc-R) and Their Unique Potential in Future α-Gal Therapies - Galili, Uri (Frontiers in Molecular Biosciences, 2021)
The alpha-gal epitope is a carbohydrate antigen which appeared early in mammalian evolution and is synthesized in large amounts by the glycosylation enzyme alpha1,3galactosyltransferase (alpha1,3GT) in non-primate mammals, lemurs, and New-World monkeys. Ancestral Old-World monkeys and apes synthesizing alpha-gal epitope underwent complete extinction 20-30 million years and mutated progeny lacking alpha-gal epitopes, survived. Humans, apes and Old-World monkeys which evolved from the surviving progeny lack alpha-gal epitopes and produce the natural anti-Gal antibody which specifically binds alpha-gal epitopes. Because of this reciprocal distribution of the alpha-gal epitope and anti-Gal in mammals, transplantation of organs from non-primate mammals (e.g., pig xenografts) into Old-World monkeys or humans results in hyperacute-rejection following anti-Gal binding to alpha-gal epitopes on xenograft cells. The in vivo immunocomplexing between anti-Gal and alpha-gal epitopes on molecules, pathogens, cells or nanoparticles may be harnessed for development of novel immunotherapies (referred to as “alpha-gal therapies”) in various clinical settings because such immune complexes induce several beneficial immune processes. These include localized activation of the complement system which can destroy pathogens and generate chemotactic peptides that recruit antigen-presenting-cells (APC) as macrophages and dendritic cells, targeting of antigens presenting alpha-gal epitopes for extensive uptake by APC, and activation of recruited macrophages into pro-reparative macrophages. Some of the suggested alpha-gal therapies, based on these immune processes are: 1. Increasing efficacy of enveloped-virus vaccines by synthesizing alpha-gal epitopes on vaccinating inactivated viruses thereby targeting them for extensive uptake by APC. 2. Converting autologous tumors into anti-tumor vaccines by expression of alpha-gal epitopes on tumor cell membranes. 3. Accelerating healing of wounds and burns by alpha-gal nanoparticles which decrease injury healing time and diminish scar formation. 4. Increasing anti-Gal mediated protection against zoonotic viruses presenting alpha-gal epitopes and against protozoa such as Trypanosoma, Leishmania and Plasmodium, by vaccination for elevating production of the anti-Gal antibody. The efficacy and safety of these therapies was demonstrated in transgenic mice and pigs lacking alpha-gal epitopes and producing anti-Gal, raising the possibility that these alpha-gal therapies may be considered for further evaluation in clinical trials.